Setting our bibliographic references free: towards open citation data. Issue 2 (9th March 2015) - Peroni, Silvio; Dutton, Alexander; Gray, Tanya; Shotton, David
Abstract : Purpose: – Citation data needs to be recognised as a part of the Commons – those works that are freely and legally available for sharing – and placed in an open repository. The paper aims to discuss this issue. Design/methodology/approach: – The Open Citation Corpus is a new open repository of scholarly citation data, made available under a Creative Commons CC0 1.0 public domain dedication and encoded as Open Linked Data using the SPAR Ontologies. Findings: – The Open Citation Corpus presently provides open access (OA) to reference lists from 204, 637 articles from the OA Subset of PubMed Central, containing 6, 325, 178 individual references to 3, 373, 961 unique papers. Originality/value: – Scholars, publishers and institutions may freely build upon, enhance and reuse the open citation data for any purpose, without restriction under copyright or database law.